Mental Health and Protective Factors for Transgender and Gender-Diverse Youths Who Trade Sex: A Minnesota Statewide School-Based Study, 2019. - Nic Rider, G.; McMorris, Barbara J.; Brown, Camille; Eisenberg, Marla E.; Gower, Amy L.; Johnston-Goodstar, Katie; Filoteo, Montana; Singerhouse, Emily; Martin, Lauren (American Journal of Public Health, 2022)
Objectives. To describe the prevalence of sex trading by gender and by associations with mental health concerns and protective factors. Methods. We used data from 9th and 11th graders who completed the 2019 Minnesota Student Survey. The analytic sample (n = 67 806) included transgender and gender-diverse (TGD) youths and cisgender youths who reported trading sex. Data on 7 mental health measures and 4 school-related and health care–related protective factors were collected. Results. The prevalence of sex trading (5.9%) was 5 times higher among TGD students than cisgender students (1.2%). In addition, the prevalence of all mental health concerns was high among TGD students who traded sex (e.g., 75.9% reported a lifetime suicide attempt, as compared with 45.9% of cisgender students who traded sex). Fewer statistical differences were found across protective factors. When TGD students who traded sex were compared according to sex assigned at birth, no statistically significant differences were found. Conclusions. Our findings support strong calls for increased competence regarding gender and sex trading or exploitation in clinical and school-based settings to decrease health disparities among TGD youths. Public Health Implications. In this study, we have presented unique prevalence estimates of mental health disparities among TGD students in the United States who trade sex. Our results indicate that TGD students who trade sex are at risk for mental health symptoms and that sensitivity to both gender and sex trading or exploitation will be critical to meeting the needs of this group in clinical as well as school-based settings.